Determinant of income inequality: empirical study of 34 provinces in Indonesia moderated by investment - Ainul Mardhiyah; Fitrawaty Fitrawaty (Iqtishaduna: Jurnal Ilmiah Ekonomi Kita, 2025)
Purpose – This study aims to find empirical evidence of the influence of gross regional domestic product, poverty rate and human development index on income inequality in Indonesia from 2016 to 2023 moderated by investment. Method – This study uses a quantitative approach with secondary data obtained through the official website of Statistics Indonesia. The population of this study consists of 34 provinces in Indonesia. The sample used is 272 data observations obtained from a combination of the number of provinces and years of research. The data analysis used is the panel data regressions and moderated regression analysis (MRA) method with EViews 12. As a result of the Chow and Hausman tests, the random effect model is the selected model. Findings – The research findings indicate that income inequality is positively affected by gross regional domestic product, poverty rate, and human development index. In contrast, investments do not affect income inequality. Investment cannot moderate the influence of gross regional domestic product, poverty rate, and human development index on income inequality. Implications – The study findings contribute to the scientific understanding of income inequality determinants in Indonesia as a low-middle income country. The practical implications of these findings for policymakers are expected to increase economic growth, improve education and healthcare quality, reduce income inequality and unemployment, and maintain price stability and purchasing power for the community.